Prevalence of yeasts in the oral cavity of children treated with inhaled corticosteroids - Komiyama, Edson Yukio; Ribeiro, Patrícia Monteiro; Junqueira, Juliana Campos [UNESP]; Koga-Ito, Cristiane Yumi; Jorge, Antonio Olavo Cardoso [UNESP] (FapUNIFESP (SciELO), 2004)
The aim of this study was to observe the prevalence of Candida spp. in the oral cavity of children undergoing treatment with inhaled corticosteroids. Thirty children treated with inhaled corticosteroids and thirty control children were studied. Saliva samples were collected through oral rinses with phosphate buffered saline (PBS). The samples were plated on Sabouraud's dextrose agar and incubated at 37 degrees C for 48 h. After this period, the number of colony-forming units per ml (cfu/ml) of saliva was calculated. The isolates were identified by phenotypic characterization. Candida spp. was isolated from 43.33% of the samples of children treated with corticosteroids, with a mean of 780 cfu/ml of saliva, and from 30% of the samples of the control group, with a mean of 560 cfu/ml of saliva. No significant statistical difference was observed between the groups. C. albicans was the prevalent species in both groups, followed by C. guilliermondii, C. parapsilosis and C. stellatoidea. Furthermore, Rhodotorula rubra and C. lusitaniae were also isolated from the treated group. We concluded that there was no significant increase in the prevalence and number of Candida spp. in the oral cavity of children treated with inhaled corticosteroids.
Keywords: corticosteroid; asthma; bacterial count; Candida; case control study; child; classification; human; inhalational drug administration; isolation and purification; microbiology; preschool child; prevalence; saliva; Administration, Inhalation; Adrenal Cortex Hormones; Asthma; Case-Control Studies; Child; Child, Preschool; Colony Count, Microbial; Humans; Prevalence; Saliva